An Analysis of Multilevel Factors Affecting Life Skills in the 21st Century of 11th Grade Students in School under the Office of Secondary Educational Service Area 33 - Thongma, Bungon; Wisaprom, Methee; Suphat, Pakornchai; Sihawong, Jittimaporn (Journal of Education Rajabhat Maha Sarakham University, 2020)
The purposes of this research were: 1) To study factors in the student level, 2) to study factors in classroom level, and 3) Developing prediction equations to predict factors level of students and classroom affecting life skills in the 21st century of grade 11th students in school under the Office of Secondary Educational Service Area 33. The sample was 1,045 students in 1st semester of the 2017 academic year by multi-stage random sampling technique and 1 teacher per 1 class from 39 classes. The research instrument was a questionnaire and test statistics consisted of multiple regression analyses within the level and multiple regression analysis between level by the statistical package. The research revealed that 1) factors in student level included Self-concept (SEL), Achievement (ACH) motivation and taking care (PAR), which was found significant at 0.01, 2) factors in classroom level was student centered learning (LEA) with significant at 0.01, and 3) The Forecast equation of factor in student level by using multilevel analysis were as follow: Multiple model in student level was Ý = -4.974 + 0.050PAR + 0.225ACH + 0.521SEL and the standard score was ZÝ = 0.059ZPAR + 0.247ZACH + 0.635ZSEL Multiple model in classroom level was oj = -4.974 + 0.403LEA and the standard score was Z oj = 0.909ZLEA